Numerical and experimental assessment of ductile fracture in tensile and compressive-dominant processes - Vaz Jr. M.* (2006)
Failure prediction in fracture-free materials under a general stress-strain path has posed a great challenge to researchers. Despite the fact that numerical assessment of ductile failure under tensile stress states has been reasonably well described in the literature, definition of a failure criterion or modelling approach capable of successfully predicting fracture onset under a general stress-strain path has still been the object of intense research. This work presents a computational strategy to predict ductile failure onset in both compressive and tensile-dominant processes using fracture criteria based on damage models. The finite element formulation accounts for an elasto-plastic, fully coupled damage material model and the solution algorithm uses an implicit time integration scheme. The numerical predictions are validated against experimental results for tensile and upsetting tests. © 2006 Elsevier B.V. All rights reserved.